Welfare & Competition. - Scitovsky, Tibor (Routledge library editions. Economics, 2013)
Dealing with general economic theory, other than employment theory, the book discusses the theory of pure and monopolistic competition - with a special emphasis upon welfare aspects. Beginning with an analysis of the consumer and of the individual firm, the main stress is nevertheless placed on the analysis of the economic system as a whole.